Candidiasis Types, Causative Agents, and Treatment Methods - Jafar, Furdos N. (Scientific Journal of Medical Research, 2021)
Objectives: This review aimed to spotlight an important fungal infection called candidiasis caused by candida, explaining the main type of candidiasis and the species considered a causative pathogen agent with the study of the treatment methods. Conclusion: Candidiasis is a common yeast infection, and the species Candida albicans is most prevalent, candida is normal flora in the skin, mouth, and vagina, and can transfer to the pathogen causing candidiasis in immunocompromised Patients and is mainly treated by using of synthetic antifungal and sometimes medicine plant used in treatment successfully.